Roles of logistics service quality in shaping generation Z customers’ repurchase intention and electronic word of mouth in E-commerce industry - Thi Thuy An Ngo; Gia Khuong An; Dang Khoa Dao; Ngoc Quynh Nhu Nguyen; Ngoc Yen Vy Nguyen; Bao Han Phong (PLoS ONE, 2025)
As e-commerce continues to reshape retail landscapes, logistics service quality (LSQ) has become a crucial determinant of customer trust, satisfaction, and long-term engagement. This study investigates the impact of logistics service quality (LSQ) dimensions on the behavioral intentions of Generation Z consumers within Vietnam’s rapidly expanding e-commerce sector. The research focuses on how various LSQ factors—timeliness, personal contact quality, order accuracy, order condition, order discrepancy handling, and return convenience—affect trust and satisfaction, which subsequently influence repurchase intention and electronic word-of-mouth (eWOM). A quantitative approach was employed, gathering data from 495 Generation Z consumers with prior online shopping experience. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the proposed model and its hypotheses. This study found that key LSQ attributes play a significant role in shaping both trust and satisfaction, which, in turn, drive repurchase intention and eWOM. However, the findings indicate that Generation Z’s expectations for seamless logistics experiences vary across different service attributes. While factors such as order accuracy, order condition, and order discrepancy handling contribute to satisfaction, they do not necessarily build trust, highlighting the generation’s high standards and perception of these aspects as fundamental rather than differentiating features. This study challenges traditional LSQ frameworks by highlighting the evolving expectations of digital-native consumers. It offers practical insights for e-commerce businesses, emphasizing the need for a strategic blend of technological efficiency, personalized interactions, and seamless post-purchase services to enhance customer loyalty and competitiveness in the digital marketplace.